PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN BUDAYA MAPALUS PADA MASA PANDEMI COVID-19 DI DESA PICUAN SATU KECAMATAN MOTOLING TIMUR KABUPATEN MINAHASA SELATAN - Sumangkut, Wendi; Mumu, Rudy; Goni, Shirley Y. V. I. (HOLISTIK, Journal Of Social and Culture, 2021)
This research aims to determine the participation of the community in the development of Mapalus culture during the Covid 19 Pandemic in Desa Picuan Satu Kecamatan Motoling Timur, Kabupaten Minahasa Selatan. The research uses descriptive design qualitative analysis. Data collection techniques used are observation, interview, and documentation. To see how community participation in Mapalus cultural development during the covid 19 pandemic in Desa Picuan Satu. Researchers use 4 indicators, namely: family, consensus deliberation, cooperation, unity and unity. Based on the results of the research shows that the culture of "Mapalus" formed and applicable in Desa Picuan Satu is very useful, especially in increasing the level of community economy. However, in its implementation, it is not necessarily obeyed by all members of the community, especially among teenagers and civil servants (civil servants). They are only seen participating in certain activities. As for members of the community who are truly obedient and uphold Mapalus culture remain active and participate in various activities. This indicates the participation of the community in the development of Mapalus culture, but not all residents of Desa Picuan Satu adhere to and uphold the culture of "Mapalus". Nevertheless, the government of Desa Picuan Satu maintains and maintains balance so that there are no divisions and differences in perception in the community. Keywords: Participation, Community, Mapalus, Pandemic Covid 19